Trust me! a case study of the International Islamic University Malaysia’s waqf fund - Sulaiman, Maliah; Adnan, Muhammad Akhyar; Megat Mohd Nor, Putri Nor Suad (International Association for Islamic Economics, 2009)
Abstract: This paper documents the development of the International Islamic University Malaysia’s waqf Fund (IIUMWF) from its inception in 1999 to the present as well as examining its accounting practice. Specifically, we examined four pertinent areas: the management of the fund, the fundraising activities (and the types of funds, waqf khass or waqf [amm), the programmes undertaken and the accounting practices of the IIUMWF. The theoretical framework is based on the Islamic concept of accountability. On this, there are two pertinent issues addressed in this study.